Pengaruh Penambahan Variasi Limbah Serat Pelepah Pisang terhadap Kuat Lentur Beton - Rohman, Ahmad; Damara, Bobby (Universitas Batanghari Jambi, 2024)
Concrete is a material that is often used for the construction of building structures, bridges and others. Concrete consists of a mixture of fine aggregate (sand), coarse aggregate (gravel), water and cement. In addition to these materials, concrete is usually also mixed with additional materials. In this study, stone banana stem fiber was used as an additional ingredient in the concrete mix. This study aims to determine the composition of the banana stem fiber mixture in concrete, as well as to determine the cracking behavior of the concrete during testing after the addition of banana stem fiber to the concrete mixture. The purpose of this study was to determine and analyze the results of the compressive strength test of concrete, normal concrete and banana fiber mixed concrete. The method used is an experimental method with variations of banana tree fiber, namely 0% (normal concrete); 0.25% and 0.5%. In this test, the specimen model was used, namely a test object measuring 60x15x15 cm. The tests carried out were the flexural strength of the concrete which was carried out after the concrete reached the age of 28 days and the shrinkage test which could be seen visually. From the results of the study it was found that the more the mixture of banana fiber waste, the flexural strength value of the concrete decreased, starting from normal concrete with a value of 49.73 MPa, a mixture of 0.25% with a value of 28.63 MPa, and a mixture of 0.5% with a value of 27.19 Mpa.